ISLAM, MORAL DAN KEMANUSIAAN - Ahmad Ali Wafi; Arini Hidayati; Ainun Zahro Hidayati; Muhammad Hori (PT. Hasba Edukasi Mandiri, 2026)
Islam is a religion revealed to humanity to convey teachings of humanity and justice for all people without distinction. Islamic teachings possess distinctive characteristics compared to previous religions, as they are universal, comprehensive, and capable of offering solutions to various social problems within society. Therefore, Islamic teachings need to be understood and implemented in a practical manner so that their values can be realized in everyday life. One of the fundamental aspects of Islamic teachings is morality, which etymologically derives from the Latin word mores, meaning habits or ways of life. Morality represents a set of values that regulate human behavior based on an understanding of what is considered good and bad. These moral values distinguish human beings from other creatures of God and place them in a noble position. Furthermore, the concept of humanity, according to the Indonesian Dictionary (KBBI), includes basic human characteristics, feelings that prevent individuals from committing reprehensible acts, and values that are worthy of humans in general. Thus, Islam positions morality and humanity as essential foundations for building a just, dignified, and civilized social life.